Cross-sectional volatility index as a proxy for the VIX in an Asian market - Futeri Jazeilya Md Fadzil; John G. O'Hara; Wing Lon Ng (Cogent Economics & Finance, 2017)
We present a cross-sectional volatility index (CSV) applied to an Asian market as an alternative to the VIX. One problem with the construction of a VIX-styled index is that it depends on the price of calls and puts, however, the CSV index may be applied to measure the volatility when no derivatives market exists. We formulate this volatility index based on observable and model-free volatility measures. We provide a statistical argument to support that an equally weighted measure of average idiosyncratic variance would forecast market return and show that this measure displays a sizable correlation with economic uncertainty.
Keywords: 330; cross-sectional volatility index; proxy VIX; idiosyncratic risk; GARCH forecast volatility